Expressions of Immune Prophenoloxidase (proPO) System-Related Genes Under Oxidative Stress in the Gonads and Stomach of the Mud Crab (Macrophthalmus japonicus) Exposed to Endocrine-Disrupting Chemicals - Ji-Hoon Kim; Kiyun Park; Won-Seok Kim; Ihn-Sil Kwak (Antioxidants, 2024)
Endocrine-disrupting chemicals (EDCs) significantly damage biological systems related to reproductive, neurological, and metabolic functions. Approximately 1000 chemicals are known to possess endocrine-acting properties, including bisphenol A (BPA) and di(2-ethylhexyl) phthalate (DEHP). This study primarily focuses on the potential effects of EDCs on the transcriptional levels of innate immune prophenoloxidase (proPO) system-related genes under oxidative stress in the gonads and stomach of the mud crab Macrophthalmus japonicus, an indicator species for assessing coastal benthic environments, when exposed to 1 µg L−1, 10 µg L−1, and 30 µg L−1 BPA or DEHP. After EDC exposure, the expression of lipopolysaccharide and β-1,3-glucan-binding protein (LGBP), a pattern recognition protein that activates the proPO system, was upregulated in the stomach of M. japonicus, whereas LGBP gene expression was downregulated in the gonads. In the gonads, which is a reproductive organ, EDC exposure mainly induced the transcriptional upregulation of trypsin-like serine protease (Tryp) at relatively low concentrations. In the stomach, which is a digestive organ, LGBP expression was upregulated at relatively low concentrations of EDCs over 7 days, whereas all proPO system-related genes (LGBP, Tryp, serine protease inhibitor (Serpin), and peroxinectin (PE)) responded to all concentrations of EDCs. These results suggest that the antioxidant and immune defense responses of the proPO system to EDC toxicity may vary, causing different degrees of damage depending on the tissue type in the mud crab.